Unilateral renal denervation improves autonomic balance in conscious rabbits with chronic heart failure - Schiller, Alicia M. (American Physiological Society, 2013)
A hallmark of chronic heart failure (CHF) is an increased sympathetic tone resulting in autonomic imbalance. Renal denervation (DNx) in CHF patients has resulted in symptomatic improvement, but the protective mechanisms remain unclear. We hypothesized in CHF, unilateral renal DNx would improve cardiac autonomic balance. The present study used conscious, chronically instrumented New Zealand White rabbits undergoing renal DNx prior to pacing-induced CHF. Four treatment groups were used: nonpace, non-DNx [Sham-Innervated (Sham-INV)], nonpace DNx (sham-DNx), pace non-DNx (CHF-INV) or pace DNx (CHF-DNx). We examined several markers indicative of autonomic balance. Baroreflex sensitivity and time domain heart rate variability (HRV) were both decreased in the CHF-INV group compared with sham-INV and were restored to sham levels by renal DNx. Power spectral analysis indicated an increase in low-frequency/high-frequency (LF/HF) ratio in the CHF-INV compared with the sham-INV, which was normalized to sham levels by DNx. To assess whether this was due to a withdrawal of sympathetic tone or an increase in parasympathetic tone, the heart rate response was measured after an intravenous bolus of metoprolol or atropine. Bradycardia induced by intravenous metoprolol (indicative of cardiac sympathetic tone) was exacerbated in CHF-INV rabbits compared with sham-INV but was normalized in CHF-DNx. Conversely, the tachycardia in response to intravenous atropine (indicative of cardiac vagal tone) was not improved in CHF-DNx vs. CHF-INV animals. Renal DNx also prevented the increase in circulating plasma NE seen in CHF-INV rabbits. These results suggest renal DNx improves cardiac autonomic balance in CHF by a reduction of sympathetic tone.